Reinforced steel I-beams: a comparison between 2D and 3D simulation - Narmashiri, K.; Jumaat, Mohd Zamin (Simulation Modelling Practice and Theory, 2011)
This study reports the accuracies of Finite Element (FE) simulations, based on two and three dimensional (2D and 3D) modelling of strengthened steel I-beams in static linear and non-linear analyses. To investigate the effects of simulation modelling methods on the accuracy of the results, 28 computer and laboratory specimens were used. To strengthen the beams, Carbon Fibre Reinforced Polymer (CFRP) and steel plates were applied, and to simulate the specimens, ANSYS software was utilized. All specimens were modelled by using shell elements or solid elements in the 2D and 3D modelling cases, respectively. The results show that non-linear and 3D simulation methods predicted the experimental results appropriately.